CATPE protocol with capture effect for RFID tag anti-collision - Xi YANG; Hai-feng WU; Yu ZENG (Tongxin xuebao)
In a passive RFID system, when multiple tags backscatter their signals to a reader simultaneously,capture ef-fect will make the reader successfully receive one of the tag signals.To enhance the identification efficiency with capture effect,a capture-aware and tag-population-estimation protocol (CATPE) for RFID tag anti-collision is proposed. The proposed protocol estimates the number of tags and the probability of capture effect,and sets an optimal frame length when the durations of slots are different. The advantage of the protocol is that it does not need search an extreme, but one-step estimates the parameters.Thus it may reduce the computational complexity.Computer simulation results show that the identification efficiency of proposed protocol is almost identical to the existing ones, but has lower computational complexity.